Bad detectives [videorecording (Blu-Ray)] - Johnson, Chris, 1982-; Aierken, Dralla; Tingley, Freya; Meskimen, Jim; Rae, Paul, 1968- (BayView Entertainment, 2023)
Two young women inherit their grandfather's detective agency and reluctantly team up to solve their murders. Called to mourn the passing of their beloved detective grandfathers, Nic O'Connell and Ping Liu soon discover that their deaths were calculated murders. Despite their mutual animosity, the granddaughters enter an uneasy partnership to solve the case. Nic and Ping partake in a twisted game with old timers, dodgy lawyers, corrupt politicians, shifty homicide detectives, capricious antique dealers and an infamous Chinese gang. As they unravel the truth, Nic and Ping find themselves in deadlier terrain.